2015
DOI: 10.1161/circ.132.suppl_3.11958
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 11958: Predicting Heart Failure With Preserved and Reduced Ejection Fraction: The International Collaboration on Heart Failure Subtypes

Abstract: Introduction: Heart failure (HF) is a major growing public health burden, and preventive strategies focused on at-risk individuals are needed. Recent initiatives have advocated for early prevention and aggressive treatment in ACC/AHA stage A/B HF, but prior HF risk prediction models remain poorly defined and validated. Moreover, risk factors for HF-specific subtypes have not yet been examined. Methods: We developed and validated separate HF risk predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(90 citation statements)
references
References 0 publications
5
78
1
6
Order By: Relevance
“…Each incident HF event was categorized as HFpEF (LVEF≥50%), HFrEF (LVEF<50%), or unclassified (no LV function assessment available at or around the time of HF event). 30…”
Section: Clinical Outcome Ascertainmentmentioning
confidence: 99%
“…Each incident HF event was categorized as HFpEF (LVEF≥50%), HFrEF (LVEF<50%), or unclassified (no LV function assessment available at or around the time of HF event). 30…”
Section: Clinical Outcome Ascertainmentmentioning
confidence: 99%
“…Although risk factors for symptomatic HF are well described, 7 , 8 early mechanisms of HF pathogenesis that may differentially impact cardiac structure and function are yet to be fully elucidated. We therefore investigated risk factors associated with isolated and combined asymptomatic echocardiographic structural, systolic, and diastolic abnormalities that predict symptomatic HF to gain insight into early mechanisms of the pathogenesis of symptomatic HF.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 , 26 However, the associations of increased BMI, increased waist circumference, and increased TG level with lower risk of isolated diastolic abnormality were in contrast to the association of increased BMI with E/e′ ratio, 26 , 27 and the prediction of HFpEF by BMI. 7 , 8 , 28 The predominant echocardiographic criterion for diastolic abnormality in the SCREEN‐HF cohort was increased LAVI in ~50% of participants, with reduced septal e′ and increased septal E/e′ ratio in <10% of participants. 5 We previously showed that BMI was associated with lower LAVI and lower e′ in univariate, but not multivariable, analyses of the SCREEN‐HF cohort, whereas BMI was associated with higher E/e′ ratio in both univariate and multivariable analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex difference is a well-established issue in a heart failure (HF) setting [ 1 , 2 ] as well as in the context of acute myocardial infarction [ 3 ]. Women with HF effectively show advanced age as compared to men, non-ischemic aetiology of HF, higher incidences of HF with preserved ejection fraction (HFpEF), and more symptomatic forms of HF [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%